1998
DOI: 10.1172/jci3338
|View full text |Cite
|
Sign up to set email alerts
|

Reduced microvascular thrombosis and improved outcome in acute murine stroke by inhibiting GP IIb/IIIa receptor-mediated platelet aggregation.

Abstract: Treatment options in acute stroke are limited by a dearth of safe and effective regimens for recanalization of an occluded cerebrovascular tributary, as well as by the fact that patients present only after the occlusive event is established. We hypothesized that even if the site of major arterial occlusion is recanalized after stroke, microvascular thrombosis continues to occur at distal sites, reducing postischemic flow and contributing to ongoing neuronal death. To test this hypothesis, and to show that micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(201 citation statements)
references
References 40 publications
6
190
1
4
Order By: Relevance
“…In an in vivo ferric chloride thrombosis model, a localized thrombus is formed by the microinjection of 6% ferric chloride. In this model, the GPIb␣-binding venom protein, alboaggregin B, prevented primary platelet adhesion, whereas GPI562, which has been demonstrated to be a potent and selective inhibitor of ␣ IIb ␤ 3 , 36,45 prevented platelet aggregation (see Supplemental Figure S1 and Supplemental Video 1 at http://ajp.amjpathol.org). In addition, alboaggregin B prevented platelet attachment to collagen under high shear flow conditions in vitro (see Supplemental Figure S2 at http://ajp.amjpathol.org), interactions previously found to be GPIb␣/vWF-dependent.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In an in vivo ferric chloride thrombosis model, a localized thrombus is formed by the microinjection of 6% ferric chloride. In this model, the GPIb␣-binding venom protein, alboaggregin B, prevented primary platelet adhesion, whereas GPI562, which has been demonstrated to be a potent and selective inhibitor of ␣ IIb ␤ 3 , 36,45 prevented platelet aggregation (see Supplemental Figure S1 and Supplemental Video 1 at http://ajp.amjpathol.org). In addition, alboaggregin B prevented platelet attachment to collagen under high shear flow conditions in vitro (see Supplemental Figure S2 at http://ajp.amjpathol.org), interactions previously found to be GPIb␣/vWF-dependent.…”
Section: Resultsmentioning
confidence: 95%
“…To inhibit ␣ IIb ␤ 3 , GPI562 (4 mg/kg), a small molecule ␣ IIb ␤ 3 antagonist, was used. 35,36 Alboaggregin-B (280 g/kg), a GPIb␣-binding venom protein purified as a 25-kDa heterodimer from C.h. horridus (rattlesnake venom) as previously described (kindly provided by A/Prof.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…69 Perhaps a key further explanation is the lack of attention to relieving microvascular obstruction, which would potentially be exacerbated by fibrinolytic therapy alone. In a recent experimental stroke model, Choudhri et al 70 showed marked sparing of brain infarction and relief of microvascular obstruction using a platelet GP IIb/IIIa inhibitor. Initial experience with GP IIb/IIIa blockade in acute stroke management had indeed been quite favorable.…”
Section: Strokementioning
confidence: 99%
“…117 A significant dose-dependent increase in debilitating hemorrhage within the ischemic regions can occur with these agents. 117,118 In keeping with the observation that specific integrin ␣ IIb ␤ 3 blockade can produce hemorrhage within the ischemic territory in animal models, a prospective phase III trial of the pan-␤ 3 inhibitor of platelet ␣ IIb ␤ 3 in ischemic stroke patients has been terminated because of safety concerns. 119 This suggests that despite salutary effects of integrin blockade at the vascular interface a more complete understanding of the mechanisms whereby adhesive events regulate blood-brain barrier integrity and leukocyte trafficking across the microvessel permeability barrier is required.…”
Section: Targeting Integrin-matrix Interactions As Potential Treatmentsmentioning
confidence: 99%